KRYTYKA STANOWISKA KOMITETU BIOETYKI PRZY PREZYDIUM PAN W SPRAWIE KLAUZULI SUMIENIA W OPIECE ZDROWOTNEJ - Jaranowski, Paweł; Pankiewicz, Olgierd (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This paper presents a critique of PAN Presidium Bioethics Committee (BC) position on conscience clause from 12 november 2013. We argue here that BC conceptions are based on a reductionist philosophy, which foundations are foreign to hipocratic medical ethics. Simultaneously we remind physicians obligations steming from the nature of patient-doctor relation, separating them from ignoble, extraneous ones. Furthermore, we outline a split between BC argumentation and laws ethical principles all together with contemporary medical knowledge We show that the resolution of conflicts surrounding the conscience clause in reproductive medicine lies not in restraint, but in recognition of dignity and right to life of the sick, also prior to birth. Concluding point given is a negative assessment of the BC position, viewed as devoted not to medical ethics, but merely to executing contracts in public health services so that they can serve any goal.